1990
DOI: 10.1017/s0031182000061321
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of macrophage-mediated larvicidal activity inEchinococcus granulosusandMesocestoides corti(Cestoda) infection in mice

Abstract: Killing of metacestodes by normal or post-infection macrophages and the regulation of this activity by cytokines were studied in vitro. The protoscolecidal activity of normal macrophages against Echinococcus granulosus was inhibited by a product of naive T-enriched lymphocytes co-cultured with protoscoleces (PSC). By contrast, supernates from co-cultures of Mesocestoides corti tetrathyridia (MCT) and T-enriched or B-enriched normal lymphocytes increased killing of MCT by normal macrophages. Larvicidal activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…It is interesting to observe that the establishment of infection was low in 43% of the individuals from the group infected with the low dose compared to the group infected with the high dose. Macrophages are pivotal cells in the immune system because of their effector and regulatory activities (16,28), and they have been proposed as effector cells against different parasites provided they are activated by IFN‐γ (15,16,29,30). Our in vitro experiments indicate that IFN‐γ‐activated adherent PEC can kill protoscoleces, probably through the release of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to observe that the establishment of infection was low in 43% of the individuals from the group infected with the low dose compared to the group infected with the high dose. Macrophages are pivotal cells in the immune system because of their effector and regulatory activities (16,28), and they have been proposed as effector cells against different parasites provided they are activated by IFN‐γ (15,16,29,30). Our in vitro experiments indicate that IFN‐γ‐activated adherent PEC can kill protoscoleces, probably through the release of nitric oxide.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of parasite killing occurs within the first 2 weeks postinfection. Activated macrophages are involved in the killing of Echinococcus PSC (8,9,24,142). Studies in vitro indicate that macrophage-dependent killing of PSC can be increased by IFN-␥ (148) and decreased by some cytokines such as IL-10 or IL-4 (142).…”
Section: Inhibition Of Cyst Growthmentioning
confidence: 99%
“…Although the host's immune system responds to M. corti (syn. vogae) infections by several mechanisms (Mitchell and Handman 1977;Jenkins et al 1990), spontaneous removal of the infection has never been observed.…”
Section: Introductionmentioning
confidence: 99%